A Particle‐Grid Method for Opaque Ice Formation. (6th May 2013) - Im, Jaeho; Park, Hanwook; Kim, Jong‐Hyun; Kim, Chang‐Hun
Abstract: This paper presents a particle‐grid method to simulate the generation of opaque ice which has air bubbles in it. Water temperature is diffused over a grid, and the exchange of dissolved air between ice and water particles is simulated. We render a particle as an air bubble if it has sufficient air. Otherwise, it is treated as a cloudy volume by distributing air into dissolved air field when the final state has been reached. In addition, our method includes a model in which heat transfer rate may change across the grid. Unlike previous models which could generate an ice volume of only fixed shapes, our approach uses signed distance function (SDF) to generate opaque ice volumes stored in containers of various geometric shapes and can render needle‐shaped or egg‐shaped bubbles.